Unchanged triclabendazole kinetics after co-administration with ivermectin and methimazole: failure of its therapeutic activity against triclabendazole-resistant liver flukes - Ceballos, Laura (2010)
The reduced drug accumulation based on enhanced drug efflux and metabolic capacity, identified in triclabendazole (TCBZ)-resistant Fasciola hepatica may contribute to the development of resistance to TCBZ. The aim of this work was to evaluate the pharmacokinetics and clinical efficacy of TCBZ administered alone or co-administered with ivermectin (IVM, efflux modulator) and methimazole (MTZ,metabolic inhibitor) in TCBZ-resistant F. hepatica-parasitized sheep. Sheep infected with TCBZ-resistant F. hepatica (Sligo isolate) were divided into three groups (n= 4):untreated control, TCBZ-treated (i.r. at 10 mg/kg) and TCBZ+IVM+MTZ treated sheep (10 i.r., 0.2 s.c. and 1.5 i.m. mg/kg, respectively). Plasma samples were collected and analysed by HPLC. In the clinical efficacy study, the animals were sacrificed at 15 days post-treatment to evaluate the comparative efficacy against TCBZ-resistant F. hepatica.